Learning in social media on Education Non formal Department : Literature Review - Elihami Elihami (Universitas Muhammadiyah Enrekang, 2022)
The objective of this research is to examine the philosophical and theoretical underpinnings of non-formal education (NFE) and to explain its current status as a significant educational force in the postmodern era. Instead of being